Exploring the Development of Teachers’ Competences in Technology-Based EMI Practices in an Indonesian Islamic School - Imani, Anugrah; Aminuddin, Muhammad; Fadillah, Ega Nur; Sulaeman, ⁠Dedi; Rohadi, Tedi (JOLLT Journal of Languages and Language Teaching, 2026)
This study aims to describe how technology-enhanced learning with an English as a Medium of Instruction (EMI) approach is implemented at an Islamis school and to explore how teachers respond to the program. In Indonesian Islamic schools, EMI is seen as a strategic effort to strengthen students’ global readiness; therefore, integrating EMI with technology supports modernization. Using a qualitative participatory design, the research involved around 50 teachers from various subjects and was carried out in three stages: training, classroom implementation, and reflection. Data were collected through observations, interviews, and documentation, then analyzed thematically using NVivo 14 with EMI, TPACK, and SWOT as analytical lenses. The findings show that technology-based EMI is progressing but still not fully effective; teachers use technology mainly for visual support and basic English exposure, but EMI practices remain limited because of frequent code-switching, technical problems, time constraints, and minimal use of interactive digital tools. Interviews reveal that teachers respond positively yet realistically: they appreciate the increased student engagement, modernized learning atmosphere, and growing professional confidence, but also acknowledge challenges such as low digital skills, limited English proficiency, and insufficient structured training. The SWOT mapping shows opportunities in institutional branding and global readiness, and threats in inadequate infrastructure, inconsistent policies, and low parental digital literacy. The study concludes that technology-based EMI in MTs Cijangkar has strong potential but is still in transition, requiring sustained professional development, better facilities, and consistent institutional support for EMI to become a stable and effective instructional practice.